Pinkalicious : story time - Kann, Victoria (New York, NY : Harper, an imprint of Harpe rCollins Publishers, 2016)
After Pinkalicious meets her favorite author, she is inspired to write her own stories and can't wait to use her imagination in a school writing festival.
Ages 4-8.
Keywords: Imagination -- Juvenile fiction; Writing -- Juvenile fiction; Schools -- Juvenile fiction